2008
DOI: 10.1111/j.1755-3768.2008.01381.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety levels of preserved and preservative‐free tafluprost are equivalent in patients with glaucoma or ocular hypertension: results from a pharmacodynamics analysis

Abstract: ABSTRACT.Purpose: Tafluprost is a new prostaglandin F 2a (PGF 2a ) derivative in development for the treatment of glaucoma. Tafluprost is the first PGF 2a analogue with a preservative-free formulation. Methods: This randomized, investigator-masked, multicentre, crossover phase III study evaluated the pharmacodynamics and safety of preserved and preservative-free tafluprost 0.0015% eyedrops administered for 4 weeks in 43 patients with open-angle glaucoma or ocular hypertension. The primary variable was change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
66
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 19 publications
9
66
0
Order By: Relevance
“…Recent studies in human volunteers have demonstrated that BAK-preserved and preservative-free formulations of tafluprost 0.0015% have a comparable systemic pharmacokinetic profile, result in a similar reduction in IOP and are both well tolerated [13,14] . The corneal penetration of preserved and preservative-free formulations of tafluprost has not yet been elucidated.…”
mentioning
confidence: 99%
“…Recent studies in human volunteers have demonstrated that BAK-preserved and preservative-free formulations of tafluprost 0.0015% have a comparable systemic pharmacokinetic profile, result in a similar reduction in IOP and are both well tolerated [13,14] . The corneal penetration of preserved and preservative-free formulations of tafluprost has not yet been elucidated.…”
mentioning
confidence: 99%
“…[41][42][43] In particular, Hamacher et al 41 in a pharmacodynamics analysis did not find statistically significant differences between BAK-free and BAKcontaining formulations in the incidence of ocular adverse events comparing preservative-free tafluprost with tafluprost containing 0.01% BAK. Also, in the work of Gross et al 42 , travoprost BAK free and travoprost preserved with BAK showed no differences in the safety and Lewis et al 43 have demonstrated no differences in the incidence of side ocular effects, comparing travoprost 0.004% containing 0.015% BAK with travoprost 0.004% BAK free.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of PF-tafluprost in glaucoma treatment has been shown in a series of phase II and III trials and its non-inferiority to latanoprost has also been reported. 25,[27][28][29] These studies showed that the preservative is not needed to provide drug efficacy. PF-tafluprost was approved for use in glaucoma in European countries in 2008 and by the US Food and Drug Administration (FDA) in 2012.…”
Section: Anton Hommermentioning
confidence: 99%
“…25,26 It can also be used in combination with beta-blockers. The efficacy and safety of PF-tafluprost in glaucoma treatment has been shown in a series of phase II and III trials and its non-inferiority to latanoprost has also been reported.…”
Section: Anton Hommermentioning
confidence: 99%